Bone Formation in Zebrafish: The Significance of DAF-FM DA Staining for Nitric Oxide Detection - Huysseune, Ann; Larsen, Ulrike G; Larionova, Daria; Matthiesen, Cecilie L; Petersen, Steen V; Muller, Marc; Witten, P Eckhard (Biomolecules, 2023)
DAF-FM DA is widely used as a live staining compound to show the presence of nitric oxide (NO) in cells. Applying this stain to live zebrafish embryos is known to indicate early centers of bone formation, but the precise (cellular) location of the signal has hitherto not been revealed. Using sections of zebrafish embryos live-stained with DAF-FM DA, we could confirm that the fluorescent signals were predominantly located in areas of ongoing bone formation. Signals were observed in the bone and tooth matrix, in the notochord sheath, as well as in the bulbus arteriosus. Surprisingly, however, they were exclusively extracellular, even after very short staining times. Von Kossa and Alizarin red S staining to reveal mineral deposits showed that DAF-FM DA stains both the mineralized and non-mineralized bone matrix (osteoid), excluding that DAF-FM DA binds non-specifically to calcified structures. The importance of NO in bone formation by osteoblasts is nevertheless undisputed, as shown by the absence of bone structures after the inhibition of NOS enzymes that catalyze the formation of NO. In conclusion, in zebrafish skeletal biology, DAF-FM DA is appropriate to reveal bone formation in vivo, independent of mineralization of the bone matrix, but it does not demonstrate intracellular NO.
Keywords: notochord sheath; osteoblasts; ossification; nitric oxide; Bone and Bones; bulbus arteriosus; zebrafish; Osteogenesis; barvení a značení; kosti a kostní tkáň; osteogeneze; zvířata; Staining and Labeling; oxid dusnatý; Zebrafish; dánio pruhované; Nitric Oxide; barvicí látky; Coloring Agents; Animals